IP teaching syllabi in Asia: should more be done? - Abdul Ghani Azmi, Ida Madieha (The WIPO Academy and the WTO Intellectual Property, Government Procurement and Competition Division, 2017)
Intellectual Property (IP) is fast becoming an important course not only in law schools but also in engineering, science and other disciplines. This paper explores the growth of IP teaching in Asia, generally, and in Malaysia, specifically. Using simple internet searches, the paper surveys the IP curricula of certain universities in the region. As not all information can be obtained from the Internet, the paper is not able to make any indepth comparison between the syllabi or make an informed decision as to whether or in what form those courses exist. From the little information obtained through the internet survey, we can distinctly classify the IP courses into several categories: foundation courses, international IP law programme, specialised master's IP programmes, professional courses and peripheral courses .The paper concludes that with technological developments and expansion of IP in international trade, IP courses and IP professors would have to adapt and change to make them relevant to the needs of the stakeholders i.e. businesses and community at large.